EFISIENSI ALOKATIF USAHATANI TANAMAN JAGUNG MANIS (Zea mays) DI KAMPUNG SUMBER BOGA DISTRIK MASNI KABUPATEN MANOKWARI - Qurrata’ayun Nurbani Wulan Oktabania Lestaluhu; Diana Nurini Irbayanti; Kunto Wibowo (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2023)
This research aims to analyze corn farming, influencing production factors, determine the level of allocative efficiency and income received by farmers in one planting season in Sumber Boga Village, Masni District, Manokwari Regency. The selection of research locations was carried out deliberately (purposive sampling) with the consideration that the area was a corn production center. The analytical methods used are linear regression analysis of corn with the Cobb-Douglass function, allocative efficiency analysis, and farmer income analysis. The research results show that simultaneously, all X variables influence corn production. Meanwhile, partially, the land area and fertilizer variables have an effect on corn production, the seed, labor and pesticide variables have no effect on corn production. The regression results show that the adjusted R2 value is 0.968 or 96.8%. This means that 96.8% of corn production is explained by variable X, while 3.2% is explained by other variables. The results of the allocative efficiency analysis show that seeds, pesticides, land, labor and fertilizer are inefficient. The research results show that the average cost of running a corn farm is Rp 1,908,927 and revenue is Rp 3,160,000, so the income received by farmers is Rp 1,251,073.